FORMULASI DAN UJI FISIK SEDIAAN KRIM KOMBINASI MINYAK BIJI JINTEN HITAM (Nigella Sativa L.) DAN EKSTRAK DAUN PEPAYA (Papaya Carica L.) SEBAGAI TABIR SURYA - Akbar Seno Syafriansyah; Muhammad Nurul Fadel; Muhammad Khudzaifi (Nusantara Hasana Journal, 2025)
Prolonged exposure to sunlight can have harmful effects on the skin, both immediate and long-term. To prevent the negative impact of sun exposure, the use of additional protective products such as sunscreen is essential. To reduce the level of damage caused by the use of synthetic materials, the use of natural ingredients can be considered as components in the formulation of sunscreen creams. This study aims to evaluate the physical quality and determine the sunscreen activity of a cream formulation combining black cumin seed oil (Nigella sativa L.) and papaya leaf extract (Carica papaya L.). The evaluation was conducted through several tests, including organoleptic testing, homogeneity, emulsion type, pH, viscosity, and SPF testing using UV-Vis spectrophotometry. The results showed that the formulation met the required standards: organoleptic tests indicated that the scent and texture of the cream remained stable, although a change in color occurred. The formulation had good homogeneity with a pH ranging from 5 to 7. The recorded viscosities were 9732 cP, 1450 cP, 3030 cP, and 4414 cP, respectively. In the SPF test, the values obtained were 0.22; 4.37; 14.23; and 20.52. Based on these results, it can be concluded that the cream combining black cumin seed oil and papaya leaf extract demonstrated good stability and exhibited effective sunscreen activity.